Hypha formation in the white-opaque transition of Candida albicans. - Anderson, J (1989)
Cells of Candida albicans strain WO-1 and related strains switch frequently and reversibly between a white-colony-forming unit (white phase) and a gray-colony-forming unit (opaque phase). Cells in the budding white phase exhibit the usual smooth round phenotype observed in other C. albicans strains, but cells in the budding opaque phase exhibit a unique elongate shape with surface pimples or protrusions. In this study, it was demonstrated that opaque cells formed hyphae at low to negligible levels in suspension cultures but could be induced to form hyphae at high levels when anchored to the chamber wall of a perfusion chamber or to a monolayer of human skin epithelial cells. Variability in the proportion of hyphae formed between experiments appeared to be due to variability between individual opaque clones. The hyphae formed by opaque cells were morphologically identical to hyphae formed by white cells (i.e., they were devoid of pimples or protrusions and exhibited the same shape and septal locations). They also did not stain with an opaque-specific antiserum which differentially stained opaque budding cells in a punctate fashion. However, when stimulated to form buds, opaque hyphae formed opaque-shaped daughter buds, demonstrating that although they are morphologically similar to hyphae formed by white cells, they are genetically opaque.